Employer Branding: The Power of Attraction in the EB Group - Santos, Vasco Ribeiro; Monteiro, Beatriz; Martinho, Filipa; Reis, Isabel Pinto dos; Sousa, Maria JosÃ© (Journal of Reviews on Global Economics, 2019)
Employer branding of companies, organisations, and firms have recently been in focus as an essential dimension in the process of recruitment facilitating the attraction and retention the best talents. The purpose of this study is to examine the power of attraction of the EB Group, as an employer brand, considering the perception that students who attend higher education have about it. A self-administered survey was collected from 100 university students in Portugal. The results show that the EB Group has a strong brand. Furthermore, it is also an organization recognized not only for the quality of its products, as well as for the concern for customers. This study also proposes some managerial implications for companies, CEO`s, human resources and marketing directors, and further research directions within this article.